A Data Processing Methodology to Analyze Construction and Demolition Dynamics in the European Metropolis of Lille, France - Cédric Mpié Simba; Emmanuel Lemelin; Eric Masson; Ahmed Senouci; Walid Maherzi (Buildings, 2023)
In the absence of industry data, organisms, and researchers leverage free and available data, specifically building and demolition permits. Geospatial processing is essential to integrate information from various files into a single GIS layer containing all relevant attributes for analysis. This article proposes a Geographic Information System (GIS) processing model aimed at monitoring construction and demolition dynamics in the European metropolis of Lille to quantify the urban production of mineral waste from buildings. Author methodology is based on that that the deposit potential can be analyzed using the observation of the spatiotemporal dynamics of building and demolition permits. The results demonstrate that combining construction and demolition (C&D) permits with other GIS layers allows us to produce data to quantify demolition surfaces per year in a given French area. The applicability of this methodology extends to all French regions, providing insights into the impact of crises on deconstruction activities and C&D waste generation. The study focuses on C&D French public data bases (French government and European Metropolis of Lille) attributed to the region (area) of the European Metropolis of Lille (MEL) between 2013 and 2022. Some data for 2022 were incomplete due to ongoing treatment, emphasizing the importance of understanding the dynamics of demolition rates or surfaces to identify data gaps or errors. Historical trajectories of C&D permits were quantified and analyzed, revealing over 21,000 permits granted from 2013 to 2022, categorized by site type (new construction, rehabilitations, prior declarations, and demolitions). Construction sites during this period covered approximately 3,345,948 m2, constituting 20% of the MEL’s building stock, while demolition sites amounted to 1,977,911 m2, equivalent to 5% of the total area of buildings in the metropolis. Employing GIS allowed for a spatial analysis, visualizing data by municipality, urban fabric, and year. The analysis highlighted territories with high and low potential for demolition and construction, as well as the most impacted urban fabrics and dynamic periods. The article discusses potential crisis impacts (e.g., COVID-19 or economic downturns) and the implications of incomplete data. Finally, the study demonstrates how these findings can be utilized to quantify C&D waste, leveraging GIS and the production rate calculation method (GRC).